Kommunikasienavorsing in Suid-Afrika - Gustav Puth (Communicare)
THE article represents an overview of com-munication research undertaken in South Africa during the period 1974-1984. Be- cause of the relatively short history of the discipline in this country, a penetrating ana- lysis is hardly possible. Some interesting trends with regard to the distribution pat- terns of the research purposes (degree/ non-degree) and the emphases within specific subdisciplines, could however be Identified.